The Application of Digital Marketing to MSMEs Mandiri Maju Jaya Store - Suyono Saputra; Putri Wulandari Rangkuti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's era, technological progress is inevitable, because everything and matters involve technology, from education, the economy, and the business world, to our daily lives. In the practical work carried out by this writer, the aim is to the application of Digital Marketing to MSMEs at Mandiri Maju Jaya Stores. Data collection was carried out by the author in a qualitative way, namely by observation, interviewing, and documenting. with an increase in the average monthly income of MSMEs, this increase was triggered by the many offers and promotions that were disseminated through social media that had been made by the author for Mandiri Maju Jaya Stores which had the aim of supporting sales and attracting customers to MSMEs Mandiri Maju Jaya Store.